Internalisasi Nilai-Nilai Muhammadiyah: Upaya Menangkal Praktek Radikalisme Melalui Pengajaran Qira’ah di Perguruan Tinggi (Studi Atas Buku Al-Arabiyyah Al-Muyassarah Al-Darsu Al-Tsalatsun Karya Mustafa Muhammad Nuri) - A Fajar Awaluddin (Equilibrium: Jurnal Pendidikan, 2017)
Abstract. The practice of radicalism and extremism against religion in Indonesia has spread to all levels of society including students. Therefore need filtering to overcome the problem. One of them by internalizing the values of Muhammadiyah in Higher Education. This paper aims to describe the Muhammadiyah values contained in Arabic Islamic texts in the teaching of Qira'ah courses in STKIP Muhammadiyah Bone. The approach used in this paper is the analysis of two texts from a book entitled al-Arabiyah al-Muyassarah by Mustafa Muhammad Nuri using an analytical blade from Dell Hyme's theory. If associated with the conditions in Indonesia, the contents of the two texts make a significant contribution to the internalization of Muhammadiyah values namely Idil Platform, Normative Foundation and Platform of Embodiment. Based on the results of the study, the teaching of Reading with Islamic themes based on the values of Muhammadiyah gives a good impact on the students which in turn can contribute to the prevention of the behavior of radicalism and extremism against Indonesian religion and nation.Keywords: Muhammadiyah, Radicalism, Qira'ah Text, Dell Hyme Theory.